Public Policy for Regulating the Congestion in Delivery Rooms in Israel: Alternatives, Consequences, and Recommendations - Erez Cohen (Societies)
The growing congestion in delivery rooms in Israeli hospitals is the underlying issue of the current study. Aim: The study sought to examine various alternatives for public policy aimed at reducing congestion. The choice of Israel as a case study derives from its conspicuous imbalance between supply and demand in the maternity, resulting from the high demand for prenatal and birthing services on one hand and the low supply, both in absolute terms and relative to OECD countries, of medical resources such as physicians, nurses, and hospital beds. The research combines quantitative research that includes analysis of data related to human resources and hospital beds in Israel compared to other countries on one hand and data on productivity and childbirth in Israel on the other, and qualitative research that includes examination of the different alternatives to hospital-based birth. The research findings present fertility and birth data for Israel in the last decade, which are leading to increased congestion and crowding in delivery rooms and maternity wards at local hospitals. Discussion: Two possible alternatives are proposed for designing and implementing public policy capable of contributing to the regulation of this congestion. One is the home birth, and the second is private birthing centers. The research conclusions indicate that policymakers in Israel must anticipate the increasing congestion in hospital delivery rooms and maternity wards and expedite efforts at designing alternative solutions before the emergence of a crisis situation that will make it essential to identify immediate solutions.